In-vitro degradation of Czapek and molasses amended post-harvest sugarcane residue by lignocellulolytic fungal strains - Maza, Marianela (2015)
Post-harvest sugarcane residue (SCR), deposited on sugarcane fields after green harvesting, could serveas a substrate for fungal biomass and lignocellulolytic enzymes production. In the present study, themycelial growth of six strains (Trametes sp. YeH11, Bjerkandera sp. Y-HHM2, Phanerochaete sp. Y-RN1,Pleurotus sp. Y-RN3, Myrothecium sp. S-3.20 and Hypocrea nigricans SCT-4.4) was measured in-vitro byapplying a modified Gompertz equation. In-vitro assays showed shorter lag phases for fungi in modifiedCzapek, 0.3% and 1.0% molasses amended post-harvest SCR. Further increments in molasses concentrationsproduced a reduction on the specific growth rates for all tested fungi. Fungal degradation ofpost-harvest SCR and the concomitant enzyme production were tested under solid-state fermentation(SSF) of Czapek or molasses amended post-harvest SCR. Under SSF, Pleurotus sp. Y-RN3 produced thehighest laccase titers but no hydrolytic activity could be detected. Trametes sp. YeH11 and Myrotheciumsp. S-3.20 showed high endoglucanase activities. Endoxylanase production was detected exclusively inCzapek amended media. These findings have implications for the fungal treatment of post-harvest SCRand its potential impact on the use of these residues in the production of biofuels and ligninolyticenzymes.